Pengaruh Motivasi Kerja terhadap Kinerja Perangkat Nagari dalam Pengelolaan Keuangan Nagari di Kecamatan Sungayang Kabupaten Tanah Datar - Ratu Novia (Faculty of Social Science, Universitas Negeri Padang, 2017)
This study aimed to determine the influence of work motivation on the performance of government apparatus nagari in nagari financial management in the Subdistrict of Sungayang, Tanah Datar Regency. This study was conducted with quantitative approach. The population of this research was all nagari government apparatus in Sungayang Subdistrict, Tanah Datar Regency consisting of nagari secretary, nagari treasurer and five head of nagari affair. The sample in this study consisted of 32 respondents determined by Slovin formula and Simple Random Sampling technique. The data of this study were collected through questionnaire with Likert scale measurement. The data of this study were analyzed with simple linear regression test. The results of this study indicated that work motivation variable significantly influenced the performance of nagari government apparatus in financial management with a significance value of 0.000, and the Adjusted R Square value of 0.685. This means that the effect of work motivation variable on the performance of nagari financial management in Sungayang Subdistrict Tanah Datar was 68.5%. While the remaining (31.5%) influenced by other variables that are not investigated in this study.